2002
DOI: 10.1046/j.1445-2197.2002.02313.x
|View full text |Cite
|
Sign up to set email alerts
|

Malignancies of the external auditory canal and temporal bone: A review

Abstract: Carcinoma of the external ear canal is rare and, in Australia, is often related to recurrence of periauricular cutaneous malignancy. Surgical extirpation with clear margins provides the best survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…Surgical margin status was significantly correlated with overall survival, confirming prior reports 7, 10. Patients with negative margins had significantly better survival than did patients with positive margins ( P = .035).…”
Section: Resultssupporting
confidence: 86%
“…Surgical margin status was significantly correlated with overall survival, confirming prior reports 7, 10. Patients with negative margins had significantly better survival than did patients with positive margins ( P = .035).…”
Section: Resultssupporting
confidence: 86%
“…Functional considerations, such as attempted preservation of facial nerve or middle and inner ear structures, are plausible explanations. Whereas the realization of negative margins is a major goal in surgery with curative intention, resection of the tumor led to positive margins in 17% to 59% of cases reported in the literature . In the group studied here, surgery with curative intention led to clear surgical margins in 55.9% of the patients, placing the rate of successful surgical procedures at the upper range of previous reports.…”
Section: Discussionmentioning
confidence: 42%
“…Whereas the realization of negative margins is a major goal in surgery with curative intention, resection of the tumor led to positive margins in 17% to 59% of cases reported in the literature. 5,13,17,18,22,26,27 In the group studied here, surgery with curative intention led to clear surgical margins in 55.9% of the patients, placing the rate of successful sur-gical procedures at the upper range of previous reports. An unexpected finding was the resulting 5-year survival rate of 56.6% in patients with R1 status, being only marginally inferior to patients with R0 status who achieved 59.4%.…”
Section: Discussionmentioning
confidence: 59%
“…Several studies reported that radical en bloc excision creating tumor-free margins provides the best chance of survival. 16,19,64 Furthermore, Spector 65 reported that postoperative radiotherapy did not benefit patients with positive margins after resection. This suggests that a radical operation such as STBR is reasonable if en bloc resection leaving a tumor-free surgical margin is possible.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies agree that the en bloc resection with tumor-free margins is a reasonable first choice for temporal bone malignancies that are resectable. 5,7,[16][17][18][19][20][21] The procedure of STBR remains challenging because of the complex anatomy. There have been few reports on the surgical anatomy involved in this procedure.…”
mentioning
confidence: 99%